Effectivity Test of Compost Added By Coca-Cola Solid Waste Sludge With Water Spinach (Ipomoea Reptans POIR.) As an Indicator - Arthagama, I Dewa Made; Bimantara, Putu Oki; Gunasih, Ni Made Tri; Narka, I Wayan (International Journal of Biosciences and Biotechnology; Vol 11 No 1 (2023): International Journal of Biosciences and BiotechnologyDO - 10.24843/IJBB.2023.v11.i01.p03, 2023)
Effectivity test of compost fertilizer added with Coca-Cola solid waste sludge with an indicator of water spinach ( Ipomoea reptans POIR.), aiming to determine the effectiveness of the dose of compost added with Coca-Cola solid waste sludge to increase the yield of water spinach and improve some soil chemical properties. This research is a pot experiment in a greenhouse that was carried out in Kerambitan village, Tabanan region, Bali, Indonesia. Using a completely randomized design (CRD) consisting of 7 doses of compost added by Coca-Cola solid waste sludge. The compost that was used as a treatment was compost that had been added 20% of Coca-Cola solid waste sludge. The doses of compost tested were: K0 (control), K1 (3 tons of compost), K2 (6 tons of compost), K3 (9 tons of compost), K4 (12 tons of compost), K5 (15 tons of compost), Ka (250 kg urea + 50 kg phonska) per hectare, and each treatment was repeated 4 times so that 28 experimental pots were conducted. Parameters observed included: maximum plant height (cm), fresh plant weight at harvest, relative agronomic effectivities (RAE), oven-dry plant weight, soil pH, soil organic carbon (SOC), and soil CEC at harvest. Observational data were statistically analyzed, to determine the effect of the treatment being tried. If the treatment has a significant effect, then continue with the Duncans 5% test. The statistical analysis showed that the treatments had a significant effect on plant height growth, fresh and oven-dry weight of plants, as well as on some soil chemical properties. The heaviest fresh plant weight was obtained in treatment Ka (98.41 g), followed by K5 (98.35 g), K3 (98.33 g), and K4 (98.21 g) per pot. The highest value of relative agronomic effectiveness (RAE) was obtained in K5 (99.63 %), followed by K3 (99.58 %), and K4 (98.76 %). While the highest CEC was obtained in the treatment of K5 (40.25 me 100 g -1 ), K3 (39.75 me g -1 ) with successive organic-C levels (31.75%), (3.16 %) and pH (7.04), (7.0). The best dose of compost treatment from the results of this study was found in the K3 treatment (9 tons of compost ha -1 ).